The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0104-1169.0482.2645
|View full text |Cite
|
Sign up to set email alerts
|

Governance of professional nursing practice in a hospital setting: a mixed methods study

Abstract: Objective: to elaborate an interpretative model for the governance of professional nursing practice in a hospital setting. Method: a mixed methods study with concurrent triangulation strategy, using data from a cross-sectional study with 106 nurses and a Grounded Theory study with 63 participants. The quantitative data were collected through the Brazilian Nursing Work Index - Revised and underwent descriptive statistical analysis. Qualitative data were obtained from interviews and analyzed through initial, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
0
16
0
6
Order By: Relevance
“…9 A recent example of research from Brazilian nursing based on the mixed approach in concomitant triangulation was the study of the governance of the nursing practice in the hospital environment. 14 In this investigation, the collection of quantitative and qualitative data was concomitantly extracted by a validated questionnaire, by means of grounded theory. The authors demonstrated the procedures for collection (concomitant), data analysis and the fusion of both, concluding, based on the final construct of the analyzed data, that care management is the core of the nurses autonomy in a hospital setting; and that this professional uses the development of skills, experience and good professional examples to overcome the daily adversities in their working environment.…”
Section: Research Strategies In Creswell's Mixed Methods: Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A recent example of research from Brazilian nursing based on the mixed approach in concomitant triangulation was the study of the governance of the nursing practice in the hospital environment. 14 In this investigation, the collection of quantitative and qualitative data was concomitantly extracted by a validated questionnaire, by means of grounded theory. The authors demonstrated the procedures for collection (concomitant), data analysis and the fusion of both, concluding, based on the final construct of the analyzed data, that care management is the core of the nurses autonomy in a hospital setting; and that this professional uses the development of skills, experience and good professional examples to overcome the daily adversities in their working environment.…”
Section: Research Strategies In Creswell's Mixed Methods: Reflectionsmentioning
confidence: 99%
“…The authors demonstrated the procedures for collection (concomitant), data analysis and the fusion of both, concluding, based on the final construct of the analyzed data, that care management is the core of the nurses autonomy in a hospital setting; and that this professional uses the development of skills, experience and good professional examples to overcome the daily adversities in their working environment. 14 Another study of Dutch origin, reports that concomitant triangulation would be applied to conduct data collection with equal weight attribution. 15 In this research under construction, whose subject focuses on advanced nursing practices with the aim to advance authority over procedures traditionally recognized as being performed by doctors, the authors contribute with a very interesting illustrative delineation about triangulation and report using the data added to them, concomitantly collected with several techniques to infer their conclusions.…”
Section: Research Strategies In Creswell's Mixed Methods: Reflectionsmentioning
confidence: 99%
“…The Index measures characteristics of nurses' practice environment. [17] The qualitative study showed that "governance in nursing is based on managing nursing care and services. To perform these tasks, nurses seek to get around organizational support constraints and develop management knowledge and skills".…”
Section: Perception Of Ubcs and Sgmentioning
confidence: 99%
“…To perform these tasks, nurses seek to get around organizational support constraints and develop management knowledge and skills". [17] (p. 1029) The results from the Index showed that nurses within SG organizations perceived themselves to have autonomy, control over the environment, and positive relationships with physicians.…”
Section: Perception Of Ubcs and Sgmentioning
confidence: 99%
See 1 more Smart Citation